Pendampingan Pengelolaan Perpustakaan Digital untuk Memperkuat Literasi di SD Pusaka Rakyat 02 - Khusnul Fatonah; Mujazi Mujazi; Irma Damayantie (Pusat Riset dan Inovasi Nasional, 2023)
The main problem in literacy faced by SD Pusaka Rakyat 02 is the absence of library space and limited reading books owned by the school. The purpose of this activity is to provide digital library management assistance to strengthen literacy and overcome the absence of physical library space. The methods used in this activity include interviews, observations, discussions, presentations, questions and answers, and simulations. The result of this activity is that the teachers can manage the digital library well and gain experience in literacy, especially digital literacy. In addition, digital libraries can also support the learning process in the classroom, motivate students to read a variety of books, and support literacy activities in elementary schools.